2011
DOI: 10.1289/ehp.1002233
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Change and Children’s Health: Threats and Strategies for Prevention

Abstract: BackgroundGlobal climate change will have multiple effects on human health. Vulnerable populations—children, the elderly, and the poor—will be disproportionately affected.ObjectiveWe reviewed projected impacts of climate change on children’s health, the pathways involved in these effects, and prevention strategies.Data sourcesWe assessed primary studies, review articles, and organizational reports.Data synthesisClimate change is increasing the global burden of disease and in the year 2000 was responsible for >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
1
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(247 citation statements)
references
References 100 publications
2
212
1
18
Order By: Relevance
“…18 Effects on children as reported by our study include sickness, poor growth, and malnutrition. This corroborates another study, 19 which was carried out among children that documented the deleterious effects of CC on their respiratory system. Risky practices our respondents felt contributed to the occurrence of CC included smoking (a tenth), bush burning (a third), and tree felling (two-fifths).…”
Section: Discussionsupporting
confidence: 90%
“…18 Effects on children as reported by our study include sickness, poor growth, and malnutrition. This corroborates another study, 19 which was carried out among children that documented the deleterious effects of CC on their respiratory system. Risky practices our respondents felt contributed to the occurrence of CC included smoking (a tenth), bush burning (a third), and tree felling (two-fifths).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore it is important to know the level of understanding among people how they link environmental change and health problems. Several studies showed that children are worst victim of climate change [11] [12]. Some studies has been carried out both in developed and developing countries to understand the perceptions on the effects of climate change on health among communities [13]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…13 These changes pose significant threats to human health, 14 with children representing a uniquely vulnerable group. 15 According to the World Health Organization, more than 88% of the existing burden of disease attributable to climate change occurs in children younger than 5 years. 16 The diverse health effects of climate change have been categorized as primary, secondary, and tertiary (Table 1).…”
Section: Effects Of Climate Change On Children's Healthmentioning
confidence: 99%